no xdxdxdxdxdxxdxdxdxdxdxdxdxdxddxd
Answer:
Thanks profile
Step-by-step explanation:
Answer: B
Step-by-step explanation: You just multiplying 25 with 10 and w which can be simplified as 24(w+10) and adding with the 13.5 x 10 and 13.5 x w, which can be simplified as 13.5(10+w)
Answer:
r= 1r- eR = r
Step-by-step explanation:
r-r = ER final answer to equal r= -ER
Answer:
It is not equivalent.
Step-by-step explanation:
You have to expand the brackets :
(x-4)(x+3)
= x(x) + x(3) - 4(x) - 4(3)
= x² + 3x - 4x - 12
= x² - x - 12
Therefore, x² - x - 12 / (x-4)(x+3) is not equivalent to x² - 4x - 12.